2020
DOI: 10.1037/com0000188
|View full text |Cite
|
Sign up to set email alerts
|

Personality method validation in common marmosets (Callithrix jacchus): Getting the best of both worlds.

Abstract: Animal personality, consistent interindividual differences in behavior through time, has been intensively studied across animal taxa and particularly in nonhuman primates. Two different methods have been used to study personality: questionnaires filled out by trusted raters, following the research tradition in human personality psychology, and behavioral observations or testing, based on the behavioral ecology research tradition. Systematic research of cross-method validity has, however, brought equivocal resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 146 publications
1
19
0
Order By: Relevance
“…Common marmosets ( Callithrix jacchus ) are highly social cooperatively breeding New World primates that live in cohesive family groups in a variety of different habitats, from the Atlantic rain forest to the semiarid area of shrub forests (Garber et al, 2019) and have been studied in a variety of socio‐cognitive questions (Schiel & Souto, 2017). In recent years, these monkeys have become the focus of personality studies under lab conditions: they display consistent interindividual differences when assessed in a battery of experiments (Díaz et al, 2020; Koski & Burkart, 2015; Šlipogor et al, 2016; Tomassetti et al, 2019), observations (Martin et al, 2019; Masilkova et al, 2020; Šlipogor et al, 2020), questionnaires (Inoue‐Murayama et al, 2018; Koski et al, 2017; Weiss et al, 2020), and by using a combination of several different personality assessment methods (Iwanicki & Lehmann, 2015; Šlipogor et al, 2020). However, little is known about long‐term consistency of their personality structure, and no study to this date assessed the personality of wild common marmoset populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Common marmosets ( Callithrix jacchus ) are highly social cooperatively breeding New World primates that live in cohesive family groups in a variety of different habitats, from the Atlantic rain forest to the semiarid area of shrub forests (Garber et al, 2019) and have been studied in a variety of socio‐cognitive questions (Schiel & Souto, 2017). In recent years, these monkeys have become the focus of personality studies under lab conditions: they display consistent interindividual differences when assessed in a battery of experiments (Díaz et al, 2020; Koski & Burkart, 2015; Šlipogor et al, 2016; Tomassetti et al, 2019), observations (Martin et al, 2019; Masilkova et al, 2020; Šlipogor et al, 2020), questionnaires (Inoue‐Murayama et al, 2018; Koski et al, 2017; Weiss et al, 2020), and by using a combination of several different personality assessment methods (Iwanicki & Lehmann, 2015; Šlipogor et al, 2020). However, little is known about long‐term consistency of their personality structure, and no study to this date assessed the personality of wild common marmoset populations.…”
Section: Introductionmentioning
confidence: 99%
“…Nonhuman primate personality has usually been studied in captivity (e.g., Capitanio 1999, 2004; Koski, 2011; Masilkova et al, 2018; Šlipogor et al, 2016, 2020; Stevenson‐Hinde & Zunz, 1978; Stevenson‐Hinde et al, 1980a, 1980b; Uher & Visalberghi, 2016; Uher et al, 2008; Uher et al, 2013; Wilson et al, 2018), and, to a somewhat lesser extent, also in the wild (e.g., Fernández‐Bolaños et al, 2020; Carter et al, 2014b; Dammhahn & Almeling, 2012; Ebenau et al, 2020; Eckardt et al, 2015; Garai et al, 2016; Konečná et al, 2008; Manson & Perry, 2013). Personality trait correlations are likely maintained by mechanisms that may either constrain behavioral changes (i.e., “constraint hypothesis”; Bell, 2005; Lande, 1979) or particular traits may be selected for in some distinct environments (i.e., “adaptive hypothesis”; Bell, 2005; Lande & Arnold, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Animal personality is defined as consistent among‐individual differences in behaviour which persist through time and in different contexts (Carter et al., 2013; Koski, 2014; Réale et al., 2007) and is commonly described by several underlying personality traits, each of which reflects a particular aspect of an individual's behavioural repertoire (Carter et al., 2013; Réale et al., 2007). Personality has been documented across taxa in several recent studies (insects: Crall et al., 2018; fish: Barber et al., 2017; Jolles et al., 2019; reptiles: Horváth et al., 2019; Michelangeli et al., 2019; birds: Morinay et al., 2019; Richardson et al., 2019; mammals: Brehm et al., 2019; DeRango et al., 2019; Petelle et al., 2019), and personality traits such as activity (Michelangeli et al., 2019), exploration (Arvidsson et al., 2017) and boldness–shyness (Jolly et al., 2019; Perals et al., 2017) have been quantified using different methods under laboratory conditions and in free‐living populations in the wild (Krebs et al., 2019; Réale et al., 2007; Šlipogor et al., 2020; Tkaczynski et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is also evidence, at least for personality traits in this species, for plasticity, either via social facilitation or via social group effects (12). There also appears to be mixed evidence for the construct validity of common marmoset personality traits, that is, for convergent and discriminant validity between personality ratings, behavioral observations, and responses to behavioral tests (13). Finally, studies of common marmoset personality that relied on behavioral measures have revealed an association between a factor labeled "Inquisitiveness" and the strength of laterality (14), and various associations between factors labeled "Sociability", "Aggressiveness", and "Social Anxiety" and the binding potential of serotonin transporters in the brain (15).…”
Section: Marmosets (Callithrix Jacchus)mentioning
confidence: 99%